Hydrogen Bonding between Tetrahydrocannabinol and Vitamin E Acetate in Unvaped, Aerosolized, and Condensed Aerosol e‑Liquids - Lanzarotta, Adam; Falconer, Travis M; Flurer, Rick; Wilson, Robert A (Analytical chemistry (Washington), 2020)
Vitamin E acetate (VEA) has recently been identified as a potential chemical of concern in the investigation of e-cigarette, or vaping, product use associated lung injury (EVALI). According to the Centers for Disease Control and Prevention (CDC), most patients report a history of using tetrahydrocannabinol (THC)-containing e-cigarette or vaping products; approximately 50% of the THC-containing vaping products examined by the Food and Drug Administration (FDA) in this investigation have been found to contain VEA. This letter demonstrates that THC and VEA exist in the unvaped e-liquids, vaped e-liquids, and the aerosol produced from vaporizing the mixture, as a hydrogen bonded THC/VEA complex linked by the THC hydroxyl and VEA carbonyl groups. Additional work should therefore be considered to investigate what happens to this complex in the lungs.